Sarcopenia knowledge of geriatric rehabilitation patients is low while they are willing to start sarcopenia treatment: EMPOWER‐GR - Laure M.G. Verstraeten; Amir Mashni; Janneke P. vanWijngaarden; Carel G.M. Meskers; Andrea B. Maier (Wiley, 2024)
Abstract Background Sarcopenia is prevalent in 20-50% of geriatric rehabilitation inpatients and is associated with functional dependence and mortality. The aim is to assess knowledge of geriatric rehabilitation inpatients on sarcopenia and their willingness and perceived barriers to start treatment. Methods Enhancing Muscle POWER in Geriatric Rehabilitation (EMPOWER‐GR) is an observational cohort of geriatric rehabilitation inpatients in Amsterdam, the Netherlands. Knowledge of sarcopenia, willingness and perceived barriers to treatment were assessed with a survey among inpatients. Importance of and self‐perceived muscle health were rated using a visual analogue scale from 0 to 10. Descriptive statistics were used. Results Inpatients' (n = 157, 59.9% female) mean age was 80.5 years (SD 7.3). Sarcopenia (European Working Group on Sarcopenia in Older People 2) prevalence was 21.7%. Five inpatients (3.2%) had heard of sarcopenia and had knowledge of its definition. Median muscle health was rated as 6 (interquartile range: 4-7). After explanation of treatment options, 67.1% were willing to start resistance exercise training (RET), 61.1% a high‐protein diet and 55.7% oral nutritional supplements (ONS). Inpatients with sarcopenia were less willing (51.6%) to start a high‐protein diet compared with inpatients without sarcopenia (77.8%) (P = 0.002); there was no difference for RET and ONS. Most reported barriers to treatment were ONS dislike (17.0%), too many other health issues (13.6%), doubts about treatment effectiveness/importance (12.9%) and RET intensity/difficulty (10.2%). Conclusions Knowledge of sarcopenia was low, while the majority of inpatients showed willingness to start treatment. A dislike of ONS, RET difficulty and too many other health issues may reduce willingness to start treatment. Education is important to increase sarcopenia‐related health issues in geriatric rehabilitation inpatients.